DIFFERENTS SUBSTRATES, ENVIRONMENT AND THE PRESENCE OF APICAL BUD FOR ROOTING OF CUTTINGS FROM FIG TREE - PIO, Rafael; DALASTRA, Idiana Marina; CAMPAGNOLO, Marcelo Angelo; CELANT, Viviane Marcela (Scientia Agraria, 2008)
The objective the present work was the accomplishment of two experiments, to evaluate the rooting capacity in cuttings fig tree, of submitted the different protecting environments and through the maintenance or not of the apical bud, and different substrates. The cutting had been standardized with 10 cm and conditioned individually in expanded polystyrene trays, of 72 cells. In the first experiment, the substrate was constituted by land and sand (2:1 v/v). The treatments had been: climatized green house and green house (50% of light), and with or without the located apical bud in the extremity of the cuttings. In the second experiment, the trays had been filled by three different substrates (sand, land and sand: land 1:1 v/v), used with or without the located apical bud in the extremity of the cuttings. The same ones had been conditioned in green house. After 70 days, evidenced that the cuttings without apical bud, in climatized green house, had presented better resulted; the substrate sand: land presented a trend of being optimum substratum in the rooting of cuttings of the figs tree.